2022
DOI: 10.1093/qjmed/hcac185
|View full text |Cite|
|
Sign up to set email alerts
|

New-onset IgA nephropathy following COVID-19 vaccination

Abstract: Coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused significant economic and health damage worldwide. Rapid vaccination is one of the key strategies to curb severe illness and death due to SARS-CoV-2 infection. Hundreds of millions of people worldwide have received various COVID-19 vaccines, including mRNA vaccines, inactivated vaccines, and adenovirus-vectored vaccines, but the side effects and efficacy of most vaccines have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 77 publications
(75 reference statements)
0
29
0
Order By: Relevance
“…[ 3 ]. Nevertheless, since massive vaccination, growing numbers of clinical cases concerning glomerular diseases such as membranous nephropathy (MN) [ 4 ], IgA nephropathy [ 5 , 6 ], and minimal change disease [ 7 ], etc., have been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ]. Nevertheless, since massive vaccination, growing numbers of clinical cases concerning glomerular diseases such as membranous nephropathy (MN) [ 4 ], IgA nephropathy [ 5 , 6 ], and minimal change disease [ 7 ], etc., have been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies have shown that in respiratory illnesses, like chronic obstructive pulmonary disease (COPD), cystic brosis (CF) and asthma, a special type of immunoglobulin, called immunoglobulin A (IgA), increases in the body [53]. Further, during an attempt to prevent disease, humans were injected with serum containing IgA and satisfactory results were obtained, which indicated the usefulness of immunoglobulins against the coronavirus [54]. Also, a study by enzyme-linked immunosorbent assay (ELISA) evaluated the level of immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies in patients with the SARS-CoV-2 virus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been a series of reports of patients with IgAN in whom gross hematuria developed after SARS-CoV-2 vaccination. 7 Despite the large number of accumulated COVID-19 cases, reports of gross hematuria associated with SARS-CoV-2 infection in patients with IgAN are extremely rare, with only 1 case reported to date. 8 Here, we report the cases of 5 Japanese patients with IgAN who presented with gross hematuria after SARS-CoV-2 infection under different clinical circumstances.…”
Section: Introductionmentioning
confidence: 99%